Limitations of sniff nasal pressure in patients with severe neuromuscular weakness. Issue 12 (24th November 2003) - Hart, N; Polkey, M I; Sharshar, T; Falaize, L; Fauroux, B; Raphaël, J C; Lofaso, F
Abstract : Background: Inspiratory muscle strength in patients with neuromuscular disorders can be assessed using sniff inspiratory nasal pressure (Pnsn ) and maximum inspiratory mouth pressure (PImax ). However, the relative merits of Pnsn against PImax are not known in patients with severe neuromuscular disease. Objective: To investigate whether severity of disease modifies the relation between Pnsn and PImax . Methods: Vital capacity (VC), Pnsn, and PImax were measured in 258 patients with neuromuscular disorders. Results: Data were analysed from 241 patients, 17 being unable to perform PImax or Pnsn manoeuvres. The correlation between Pnsn and PImax was +0.94 (p<0.0001), with a mean (SD) difference between Pnsn and PImax of −4.8 (21.2) cm H2 O (the limits of agreement were 37.6 and –47.2 cm H2 O). VC (% predicted) was positively correlated with Pnsn /PImax ( r  =  +0.86; p<0.0001), with a lower Pnsn /PImax value in patients with a VC <40% of predicted than in those with a VC >40% (0.80 (0.35) v 1.04 (0.41); p<0.0001). Conclusions: PImax is greater than Pnsn in patients with a severe restrictive ventilatory defect caused by neuromuscular disease. Pnsn may not accurately reflect inspiratory muscle strength in such patients and it is thus advisable to use both tests.